Stratification and residence time as factors controlling the seasonal variation and the vertical distribution of chlorophyll‐a in a subtropical irrigation reservoir - León, José Gabriel (2016)
Reservoir trophic state is controlled by light and nutrient availability, as well as by hydraulic management and stratification pattern. In arid zone reservoirs, the inflow and outflow discharges have extreme seasonal variations which produce well‐defined cycles of filling and draining. Moreover, since stratification often occurs, epilimnion and hypolimnion renewal rates may vary producing different environmental conditions throughout the water column. These variation patterns may affect phytoplankton growth at both temporal and spatial scales. For two hydrological years, we analyzed the influence of light climate, nutrients, residence time (Tw), and stratification on phytoplankton biomass (as chlorophyll‐a [Chl‐a]) in an irrigation reservoir (276 hm3) in the arid central Andes in Argentina (33°S). The reservoir was turbid (ZSecchi: 1.4 m) with relatively high levels of dissolved nitrogen and phosphorus (60 μgP L−1 and 560 μgN L−1, respectively). Stratification occurred from mid‐spring to late‐summer, when hypolimnetic oxygen and pH decreased whereas dissolved nutrients increased. The reservoir was mesotrophic (Chl‐a: 4.6–10.8 μg L−1) and showed two semi‐annual peaks of Chl‐a (summer and winter). Depending on the water column circulation, Chl‐a was directly related to Tw for 60 > Tw > 200 and inversely to ammonia, during mixing and stratification periods, respectively. Phytoplankton development was strongly influenced by the seasonal variations of inflow/outflow and stratification. Chl‐a peaked in summer, when inflow plunged into the hypolimnion of the stratified reservoir and in the warm and mixed epilimnion algae proliferated until nutrients depletion. Alternatively, the winter Chl‐a maximum is likely to be produced by the higher concentration of nutrients combined with the turbulent mixing in the water column which acts as a mechanism that helps to overcome light‐limitation. Since stratification modifies the vertical distribution of Tw, the use of a single annual value of this hydraulic parameter to assess its effect on the reservoir trophic state results inadequate. This paper constitutes the first description of hydrologic effects on Chl‐a dynamics in a reservoir in arid central western Argentina.